Lumbar stabilization: An evidence-based approach for the athlete with low back pain - Kolber, M. J.; Beekhuizen, K. (Strength and Conditioning Journal, 2007)
This manuscript presents an overview of spinal stabilization for the lumbar spine. Emphasis is placed on the local stabilization musculature, which has received considerable support in the literature. A progressive stabilization program targeting the local stabilizing musculature is recommended for the diverse athletic population.